Transforming E-business practices and applications : emerging technologies and concepts - Lee, In, 1958- (Hershey, PA : Information Science Reference, 2010)
'This book presents an integrated view of the latest issues and technologies evolving from business transactions and support'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Electronic commerce; Technological innovations -- Economic aspects